An Improved Harmony Search Algorithm with Segmented Search. Issue 1 (May 2020) - Kang, Di-Wen; Mo, Li-Ping; Zhou, Kai-Qing
Abstract: Harmony search (HS) algorithm has received widely attention in various fields because of simple operation and outstanding performance. However, there exists some bottlenecks which hinders the further development of HS algorithm, such as easy trapping into local optimum and slow convergence velocity.This paper proposes an improvement HS algorithm by using segmented search strategy (SHS) to overcome these drawbacks. Comparative experiments reveal the proposed SHS algorithm has perfect performance, especially in high dimensions.